2015
DOI: 10.1002/pen.24200
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polymeric electrospun nanofibers for application in waterproof-breathable fabrics

Abstract: This study focuses waterproof-breathable fabric development by applying electrospun web of polyurethane (PU), PAN, and PES directly onto the substrate fabric. Advantages of textile fabrics of elastomeric nanofibrous membranes over gortex specimen are the mass production feasibility, high elastomeric properties, more body comfort parameters, and fabric production without holes and needle traces formation. In this work, we identified the PU nanofibrous membrane as the best and useful web for application in water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…PU possesses a wide range of desirable properties such as high hydrophobicity, adjustable pore structure, and reinforced mechanical properties, which have already been used in manufacturing industry . However, the waterproofness of pure PU nanofibrous membranes remains insufficient to allow them to compete with commercial membranes in practical applications .…”
Section: Introductionmentioning
confidence: 99%
“…PU possesses a wide range of desirable properties such as high hydrophobicity, adjustable pore structure, and reinforced mechanical properties, which have already been used in manufacturing industry . However, the waterproofness of pure PU nanofibrous membranes remains insufficient to allow them to compete with commercial membranes in practical applications .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [15] also argued that once viscose or cotton are used on the outer side, the fabric knitted with fine polypropylene (PP) filaments as the inner side touching the skin, has enhanced water holding capacity, wicking, and moisture vapor transmission. [4][5][6]19,20] Li et al [21] demonstrated that a reasonable equilibrium of breathable (water vapor transmission rate) and waterproof performance can be achieved by hydrophobic fibrous membranes prepared based on electrospinning technique. The impact of raw materials and knitting structure on the dynamics of water absorption in double-layered weft knitted fabrics was investigated by Bivainyt and Miku cionienė.…”
Section: Introductionmentioning
confidence: 99%
“…To prepare membranes with excellent filtration and mechanical properties, modifications are necessary. The improved methods include blending modifications , chemical modifications , and so forth . The preparation of polyethersulfone (PES) membrane by NIPS process was reported many times .…”
Section: Introductionmentioning
confidence: 99%
“…The improved methods include blending modifications , chemical modifications , and so forth . The preparation of polyethersulfone (PES) membrane by NIPS process was reported many times . Mansourizadeh et al prepared PES/cellulose acetate (CA) membrane by NIPS to enhance hydrophilicity and membrane structure for oil‐water separation, the results showed that both the water productivity and the structure improved.…”
Section: Introductionmentioning
confidence: 99%